Systemic Therapy Considerations in Older Adults With Early-Stage Breast Cancer - Claire E. Smith; Sarah L. Sammons; Christina A. Minami; Mina S. Sedrak; Allison Magnuson; Tracey O’Connor; Tammy T. Hshieh; Sydney Smith; Karen Ruderman; Kate Bak; Nancy U. Lin; Rachel A. Freedman (JAMA Oncology, 2026)
Importance The treatment of older adults with chemotherapy for early-stage breast cancer involves a complex decision-making process that weighs the competing risks of disease recurrence against the potential harms of treatment. While older adults continue to be underrepresented in therapeutic clinical trials, there is a growing body of evidence to support optimal management of each subtype of early-stage breast cancer, including novel strategies like adjuvant cyclin-dependent kinase 4/6 inhibitors in hormone receptor–positive disease, and the neoadjuvant use of pembrolizumab in triple-negative breast cancer. Observations The available evidence to support the systemic management of early-stage breast cancer in older adults with consideration of the data gaps for cytotoxic chemotherapy, de-escalated regimens, and targeted therapies is reviewed, and tools to optimize decision-making and supportive care for older adults with early breast cancer are presented. Clinicians should aim to avoid overtreatment when available evidence suggests a less intensive approach may suffice for a lower-risk cancer, and/or the patient is at high risk of serious toxic effects from chemotherapy treatment. On the other hand, undertreatment without consideration of the potential downsides may increase breast cancer–related mortality in older patients with higher-risk cancers. Conclusions and Relevance This review will help clinicians best use the available data and decision-making tools to support best practice for treating older adults with early-stage breast cancer and will highlight ongoing clinical trials aimed at optimizing medical care for this patient population.